SUBITIZING SEBAGAI KEMAMPUAN MENDASAR BAGI ANAK USIA DINI UNTUK MENGUASAI KONSEP BILANGAN - I Komang Sesara Ariyana (Purwadita : Jurnal Agama dan Budaya, 2018)
The concept of numbers is closely related to counting and arithmetic. Counting isconcerned with knowing how many of a given set of objects. To find out how many, maybe whatcan be done is just by counting one by one. However, if the set is small, say 1 to 4, or 5, then theviewer is able to state how many instantly, without counting it directly. This capability is knownas subitizing. Things relating to counting and arithmetic, should begin with an understanding ofsubitizing skills, because if we want to know how many by counting one by one, it will be lesseffective. It is possible that early children can do subitizing. Therefore, it is very important forteachers and also early children to understand the ability of subitizing as a fundamental abilityto perform calculations. With such understanding it is strongly recommended to teachers toprovide facilities that can practice the subitizing ability to early childhood. In this paper, wediscuss about the notion of subitizing, type of subitizing, what factor that make subitizing easyor hard, how the subitizing relationship with counting and arithmetic, and how to developsubitizing skills.Keywords: Arithmetic, Early childhood, Counting, Numbers, Subitizing